1995
DOI: 10.1021/tx00049a004
|View full text |Cite
|
Sign up to set email alerts
|

The Sulfoxidation of the Hexachlorobutadiene Metabolite N-Acetyl-S-(1,2,3,4,4-pentachlorobutadienyl)-L-cysteine Is Catalyzed by Human Cytochrome P450 3A Enzymes

Abstract: The sulfoxidation of the mercapturic acid N-acetyl-S-(1,2,3,4,4-pentachlorobuta-1,3-dienyl)-L-cysteine (N-Ac-PCBC), a urinary metabolite of the renal toxin hexachlorobutadiene (HCBD), was studied in human liver microsomes and with purified cDNA expressed human liver cytochrome P450 (P450) enzymes. N-Acetyl-S-(1,2,3,4,4-pentachlorobuta-1,3-dienyl)-L-cysteine sulfoxide (N-Ac-PCBC SO) is a major urinary metabolite of HCBD in male rats; only liver microsomes from male rats catalyze the sulfoxidation of N-Ac-PCBC. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…This evidence supports the hypothesis that sulfoxide 3 detected in urine is formed enzymatically and not as a result of air oxidation. Cytochrome P450 and flavin-containing monooxygenase (FMO) are two enzymes capable of oxidizing mercapturic acids to their sulfoxides, with CYP3A enzymes being the most active. …”
Section: Discussionmentioning
confidence: 99%
“…This evidence supports the hypothesis that sulfoxide 3 detected in urine is formed enzymatically and not as a result of air oxidation. Cytochrome P450 and flavin-containing monooxygenase (FMO) are two enzymes capable of oxidizing mercapturic acids to their sulfoxides, with CYP3A enzymes being the most active. …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies revealed a discrepancy in the formation and/or in the handling of N-AcPCBC-SO in rats: In incubations of N-AcPCBC with liver microsomes two diastereomers, (R)-and (S)-N-AcPCBC-SO, were formed in a 1:1 molar ratio by rat P450 3A 1/2 and human P450 3A 4/5, but after administration of HCBD to male rats only one diastereomer was found to be excreted with urine (8,9,11). To elucidate the molecular mechanism for this discrepancy, a 1:1 mixture of (R)-and (S)-N-AcPCBC-SO was given to male and female Wistar rats.…”
Section: Discussionmentioning
confidence: 99%
“…A structurally related sulfoxide derived from S-(1,2-dichlorovinyl)-L-cysteine was also shown to exhibit β-lyase-independent toxicity (10). A discrepancy, however, having not been clarified yet, was observed in both experiments (8,9,11): In incubations of N-AcPCBC with rat liver microsomes two diastereomers (R)-and (S)-N-AcPCBC-SO were formed in a nearly 1:1 molar ratio by P450 3A 1/2, but after administration of HCBD to male rats only one diastereomer was found to be excreted with urine.…”
Section: Introductionmentioning
confidence: 95%
“…Covalent binding of this reactive metabolite to macromolecules results in toxicity [133,134]. A sex-specific metabolite, N-acetyl-S-(1,2,3,4,4-pentachlorobutadienyl)-L-cysteine (N-ac-PCBC) sulfoxide, was identified in the urine of male rats treated with HCBD [43] with an apparent role of the male-specific CYP3A2 as catalyst of sulfoxidation [135]; the sulfoxidation of N-ac-PCBC is also catalyzed by human CYP3A enzymes [136].…”
Section: Hexachloro-1:3-butadienementioning
confidence: 99%